Role of dopant ions in electrocatalytic oxidation of methanol using conducting polypyrrole electrodes - Radhakrishnan, S.; Adhikari, Arindam (Journal of Power Sources, 2006)
Conducting polypyrrole electrodes obtained by electro-polymerization of pyrrole on vacuum metallized glass substrates are modified by doping with a range of metal halides as dopant ions having different electronegativity. Electro-oxidation of methanol using these electrodes is studied by means of cyclic voltammetry in 0.1 M HCiO(4) as supporting electrolyte. It is found that the electronegativity of the dopant ion plays a very important role in the electrocatalytic activity. Polypyrrole doped with zirconium chloride gives the highest anodic current of 10 mA cm(-2) at the oxidation potential of methanol. The results are explained on the basis of the charge-transfer efficiency at the electrode I electrolyte interface, which is associated with the acceptor state created by the dopant in the semi-conducting polymer. (c) 2005 Published by Elsevier B.V.
Keywords: conducting polymers; electrocatalysis; fuel cells; Methanol oxidation; polypyrrole

Influence of dopant ions on properties of conducting polypyrrole and its electrocatalytic activity towards methanol oxidation - Adhikari, Arindam; Radhakrishnan, S.; Patil, Rahul (Synthetic Metals, 2009)
The polypyrrole (PPy) films were deposited on vacuum metallized substrates by electro-oxidation of pyrrole monomer. These electrodes were then modified with a range of metal halides having different electronegativities. The modified polypyrrole electrodes were employed to investigate electrocatalytic activity towards methanol electrochemical oxidation by means of cyclic voltammetry in 0.1 M HClO(4) as supporting electrolyte. It was found that the electronegativity of the dopant ion incorporated in the PPy film governs the electrocatalytic activity towards methanol oxidation. Among different dopant anions used in the present work, the PPy doped with zirconium chloride gave the highest anodic current of 10 mA cm(-2) at the oxidation potential of methanol. Electrical property and the charge created due to doping in the polymers were measured using X-ray photoelectron spectroscopy (XPS) and Electron spin resonance spectroscopy (ESR). Electrocatalytic activity of the modified electrodes was correlated with various factors obtained from different polymer characterization experiments. The results were explained on the basis of the charge-transfer efficiency at the electrode I electrolyte interface, which was associated with the acceptor state created by the dopant in the semi-conducting polymer. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: charge transfer; electrocatalyst; ESR; Metal halide dopant; Methanol oxidation; polypyrrole; XPS

Mechanistic aspects of methanol electro-oxidation reaction through cyclic voltammetry: is it correct to blame carbon monoxide for catalyst poisoning? - Deshpande, Pooja S.; Chaudhari, Vijay R.; Prasad, Bhagavatula L. V. (Energy Technology, 2020)
The mechanism of the methanol oxidation reaction is revisited using systematic cyclic voltammetric studies. These studies clearly indicate that the peak during the cathodic scan belongs mainly to electro-oxidation of the carbon monoxide, and that only a fraction of this carbon monoxide remains adsorbed on the electrode, contrary to what previous reports suggested. More details can be found in article number by Bhagavatula L. V. Prasad and co-workers.
Keywords: carbon monoxide; cyclic voltammetry; electrocatalysts; electrode poisoning; Methanol oxidation